The nexus between leadership and the performance of the National Social Security Authority (NSSA) in Zimbabwe - Alouis Chilunjika; Dominique E. Uwizeyimana; Sharon, R.T. Chilunjika (Center for Strategic Studies in Business and Finance, 2023)
The study examined the role of leadership in the performance of the National Social Security Authority (NSSA) in Zimbabwe. The study employed mixed methods research, which triangulated qualitative and quantitative techniques. Respondents for the questionnaires were selected using simple random sampling. Participants for interviews were purposively selected. Written records were also used to collect data. Data from questionnaires were analyzed using Statistical Package for Social Scientists (SPSS), and qualitative data were analyzed using thematic and content analysis. The study established leadership as a crucial component for NSSA’s satisfactory performance, with investment activities, service delivery, and corporate social responsibility used to gauge NSSA’s performance. The study recommended the intricate interaction of the leadership and the employees and the creation of a robust corporate governance framework to do away with political prying and enhance efficiency and effectiveness in the running of NSSA.